2022
DOI: 10.1093/jn/nxac105
|View full text |Cite
|
Sign up to set email alerts
|

Association of Egg Consumption with Risk of All-Cause and Cardiovascular Disease Mortality: A Systematic Review and Dose–Response Meta-Analysis of Observational Studies

Abstract: Background Recent studies have reported conflicting associations between egg consumption and the risk of all-cause or cardiovascular disease (CVD) mortality, including ischemic heart disease (IHD) mortality and stroke mortality. With accumulating evidence, up-to-date evidence about the association should be synthesized. Objective To assess the association of the risk of all-cause and CVD mortality with egg consumption. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This was similar to earlier reviews which also found mixed results. A meta-analysis of 39 observational studies including nearly 2 million individuals found no association between the highest intake of eggs and CVD mortality [55], and similar findings were presented in another meta-analysis of 24 observational studies of over 11 million individuals that found no association between highest intake of eggs and CVD mortality [56]. However, contrasting findings were reported in a meta-analysis of 19 observational studies that found a nonlinear dose-response association between egg consumption and CVD mortality, although the certainty of the evidence for these observations was rated as very low [57].…”
Section: Discussionmentioning
confidence: 53%
“…This was similar to earlier reviews which also found mixed results. A meta-analysis of 39 observational studies including nearly 2 million individuals found no association between the highest intake of eggs and CVD mortality [55], and similar findings were presented in another meta-analysis of 24 observational studies of over 11 million individuals that found no association between highest intake of eggs and CVD mortality [56]. However, contrasting findings were reported in a meta-analysis of 19 observational studies that found a nonlinear dose-response association between egg consumption and CVD mortality, although the certainty of the evidence for these observations was rated as very low [57].…”
Section: Discussionmentioning
confidence: 53%
“…A further SRMA also found that overall consumption of each additional egg/day was associated with a small but significant increase in risk of CVD of 4% [ 51 ]. However, the other three SRMA looking at risk of CVD found no significant effects of egg consumption [ 52 , 53 , 54 ] and studies on CVD mortality largely found no association between egg intake and risk of death from CVD [ 49 , 55 , 56 , 57 , 58 ]. The exception was the SRMA by Yang et al, which reported an overall 7% increased risk of CVD mortality with each increment of 1 egg/day [ 59 ].…”
Section: Results: Risk Assessmentmentioning
confidence: 99%
“…At intakes of 1–4 eggs/week, there was a decreased risk of stroke which switched to an increased risk in those consuming 10+ eggs/week [ 62 ]. None of the studies found a significant association between egg intake and risk of stroke mortality [ 49 , 55 , 57 , 58 , 59 ].…”
Section: Results: Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 2 very recent meta-analyses addressing the association between egg consumption and mortality have been published. The first of these, with 24 observational studies, found that an additional increase of 1 egg/day in habitual consumption was associated with a modest increase (6 %) in the risk of premature mortality, especially in older people, in studies carried out with the United States population (Ma et al, 2022). The second meta-analysis, with 32 observational studies, concluded that egg consumption was not associated with all-cause mortality, cardiovascular or respiratory, but the highest consumption category, compared to the lowest consumption category, was associated with a 20 % higher risk of cancer mortality.…”
Section: Eggsmentioning
confidence: 99%